Frequency of functional esophageal disorders in patients with refractory reflux symptoms in Lima, Peru - Piza-Palacios, Luis (2023)
Gastroesophageal reflux disease (GERD) is a clinical condition in which gastric reflux causes symptoms or damage to the esophageal mucosa. It is managed with proton pump inhibitors, however, up to 45% of patients with suspected GERD are refractory to treatment. It is necessary to establish a true GERD diagnosis by means of a digestive endoscopy, which does not show lesions in approximately 70% of patients. In this scenario, it is necessary to perform an esophageal pH-impedance measurement, a procedure that allows to determine whether exposure to gastric acid is pathological. Of this group, patients with pathological acid exposure are diagnosed as true non-erosive reflux disease (NERD). If, in addition to not presenting esophageal lesions, they have a physiological exposure to gastric acid, they suffer from esophageal hypersensitivity or functional heartburn, which are functional disorders. These require a different approach from that of GERD or NERD, as the symptoms are not due to pathological exposure to gastric acid. The aim was to calculate the frequency of esophageal hypersensitivity and functional heartburn in patients with suspected NERD. This was a cross-sectional study. Data was collected by reviewing pH-impedance and manometry reports, 166 patients were selected. The frequency for functional disorders was 86.15%, being 46.9% for functional heartburn and 39.2% for esophageal hypersensitivity. The frequency of functional disorders was higher than that reported in previous studies. In conclusion, age, psychological conditions, dietary, cultural, ethnic or lifestyle factors inherent to our environment might play important roles in the development of functional disorders.